Gorbatschow, der neue Mann - Poljanskij, Nikolaj Nikolaevič 1939-; Rahr, Alexander 1959- Mitarb; Poljanskij, Nikolaj Nikolaevič 1939- Mitarb; Poljanski, Nikolai VerfasserIn; Voslensky, Michael VerfasserIn von ergänzendem Text (Universitas-Verl, 1986)
Nikolai Poljanski und Alexander Rahr: Gorbatschow. Der neue Mann. Universitas Verlag, München, 1986, 350 Seiten, 38 Mark